Tenets of Community-Engaged Scholarship Applied to Delta Ways Remembered - Bharadwaj, Lalita Anne (Engaged Scholar Journal)

(untitled) (University of Saskatchewan, 2019)
This essay reviews challenges posed to community-engaged scholars regarding tenure/promotion processes in Canadian universities, with a note to characteristics of community-engaged scholarship that were developed by Catherine Jordan (2007) to address gaps in academic assessment of engaged scholarship. These characteristics are: clear goals, adequate preparation, appropriate methods: scientific rigor and community engagement, significant results/impact, effective presentation/dissemination, reflective critique, leadership and personal contribution, and consistently ethical behavior. These are then applied to a non-peer reviewed work that describes the cumulative effects of environmental change for people in the Slave River Delta Region of the North West Territories, Canada. The reader is asked to view Delta Ways Remembered, a 13-minute video employing an enhanced e-storytelling technique to share and disseminate traditional knowledge about the delta from a compendium of people as a single-voiced narrative. The purpose is to highlight the scholarship underlying non-traditional academic expositions not readily assessed under current paradigms of academic evaluation. This essay strives to illustrate how Jordan’s characteristics can be applied to evaluate non-peer reviewed scholarly work, and also to share rewards and challenges associated with the harmonious blending of Indigenous and western knowledge addressing societal/environmental issues identified by the Indigenous community.